STUDI PERBANDINGAN TINGKAT KEPATUHAN ADOPSI INTERNATIONAL FINANCIAL REPORTING STANDARD (IFRS) DI 12 NEGARA - Devi Kharisma Dewanti; Endang Kiswara (Diponegoro Journal of Accounting, 2015)
This study aims to examine how the level of compliance of the research object in adopting IFRS. This research was conducted by using the comparative method of qualitative analysis on the companies selected to represent the 12 states research object. Selection of 12 countries was carried out by countries that are member of the IFAC (International Federation of Accountans). The results of this study showed that every country have different level of compliance in the process of IFRS adoption. The level of compliance of each country can be seen through the financial statements reported by the company. Countries that have high level of compliance, automatically has adopted almost all the component of IFRS.